(untitled) (Revista Iberoamericana de Bioética, 2022)
Abuse of the elderly is a new and growing problem in the healthcare field. Bioethics must work hand-in-hand with public health to address it. People over 60 years old were surveyed during 2020 in Argentina about their perceptions surrounding abuse. A total of 363 responses were received, of which 81% consider that they do not hold their rightful place in society and 81.3% believe that their rights are not respected. Different forms of abuse are widespread, and create and add layers of vulnerability that affect their health. Identifying abuse can lead to actions to eradicate abuse.